Conductive nanographite–nanocellulose coatings on paper. (12th July 2017) - Kumar, Vinay; Forsberg, Sven; Engström, Ann-Christine; Nurmi, Maristiina; Andres, Britta; Dahlström, Christina; Toivakka, Martti
Abstract: Paper products with active and functional coatings have attracted interest in recent years to counter the stagnating demand for traditional graphic paper grades. Conductive coatings have potential uses in various energy generation and storage applications, e.g. in batteries, supercapacitors, and photovoltaics. The current work aims to demonstrate large-scale production of flexible low-cost nanographite coatings on paper-based substrate. The large aspect ratio of graphene present in the suspension limits solids content to very low values, which makes it challenging to create thick coating layers required for high conductivity. The use of nanocellulose binder together with a custom-built slot-coating device enables roll-to-roll coating of thick conductive coatings on paper. The rheological and water-retention properties of nanographite–nanocellulose suspensions are reported. The influence of coat weight, carbon black addition, and calendering on coating structure and the resulting conductivity of the coatings is investigated. Impact of humidity and bending/creasing of coated samples on their electrical performance is explored as well. The lowest surface resistances obtained were in the range 1–2 Ohm/□ for 15 g m −2 coat weight. Increasing the coat weight and calendering nip load resulted in higher conductivity of coatings. Carbon black addition deteriorated the conductivity somewhat, probably due to increased porosity of coatings. Moisture and creasing did not affect significantly the conductivity of high coat weight and calendered samples. The results reported are very encouraging for future research on further improving the electrical performance of such carbon coatings.